Bioelectrocatalytic Electrodes Modified with PQQ‐Glucose Dehydrogenase‐Calmodulin Chimera Switchable by Peptide Signals: Pathway to Generic Bioelectronic Systems Controlled by Biomolecular Inputs. Issue 3 (4th January 2019) - Gamella, Maria; Guo, Zhong; Alexandrov, Kirill; Katz, Evgeny
Abstract: Construction of artificial allosteric protein switches is one of the central goals of synthetic biology that holds promise to transform the way we detect and quantify substances in vitro and in vivo. An artificial chimeric fusion protein of pyrroloquinoline quinone‐dependent glucose dehydrogenase with calmodulin (PQQ‐GDH‐CaM) was covalently attached to graphene nanosheets produced electrochemically on a carbon fiber electrode. The chimeric PQQ‐GDH‐CaM represents an artificial allosteric switch activated by association of a calmodulin‐binding peptide with the Ca 2+ ‐bound calmodulin domain. The activity of the immobilized enzyme was switched between active and inactive states by adding/removing the activating peptide. The peptide‐signal switchable features originated from the enzyme 3D‐structural variations induced by the conformational (folding/unfolding) changes in the connected calmodulin unit upon formation/dissociation of its complex with the specific peptide. The peptide‐activated immobilized PQQ‐GDH‐CaM enzyme displayed direct (non‐mediated) electron transfer to the conducting electrode support upon glucose oxidation. On the contrary, in the absence of the peptide, the inactive form of the enzyme demonstrated very low bioelectrocatalytic activity for glucose oxidation. Since the conformational changes of the PQQ‐GDH‐CaM depend on the presence of Ca 2+ cations and the calmodulin‐binding peptide, both of them were used as input signals to control the enzyme activity mimicking a Boolean AND logic gate. The switchable behavior of the enzyme‐modified electrode was studied electrochemically and used to assemble a signal‐switchable biofuel cell. The use of the peptide as the signaling messenger enables the design of generalizable bioelectronic systems controlled by native and synthetic biochemical signaling systems. Abstract : Switchable bioelectrochemistry : an artificial chimeric fusion of pyrroloquinoline quinone‐dependent glucose dehydrogenase with calmodulin is covalently attached to a graphene‐functionalized electrode. The chimeric enzyme represents an artificial allosteric biocatalyst. The immobilized enzyme is switched between active and inactive states by adding/removing an activating calmodulin‐binding peptide and Ca 2+ ions. The switchable electrode is used to mimic an AND logic gate and to design a signal‐switchable biofuel cell.